Optimization and evaluation of automatic rigging path guidance for tele-operated construction crane - Chi, Hung-Lin; Kang, S.; Hsieh, S.; Wang, Xiangyu (University of Technology Sydney, 2014)
The objective of this research is to develop, optimize and evaluate an approach for automatically generating rigging path guidance in order to provide sufficient assistance on the user interface of tele-operated crane. Besides operational safety and efficiency, this approach focuses on solving operability issues of following path guidance on a tele-operated crane system. To provide path guidance that can realistically be performed in a tele-operated rigging scenario, three factors are proposed for consideration in the development of such an approach: Visibility, Control Features, and the Dynamic Environment. A simulation platform in the virtual environment, called PathGuider, is developed for evaluating the use of the proposed path guidance considerations. Demonstrations for visibility and the dynamic environment issues have been performed and they show that the guidance path can be re-planned in real-time once the guided trajectories are being sheltered by surrounding buildings from operators' view or dynamic objects interfered with it. To evaluate the efficiency of the developed re-planning algorithm, a benchmark has been developed. The results show that the calculation time of cases considered are all within real-time span. The proposed path guidance approach reveals its efficiency and feasibility in providing useful assistance to tele-operated crane's operators.